A study of hydraulic characteristics for flow in equatorial rivers - Lai, Sai Hin; Mah, Yau Seng; Nabil, Bessaih; Law, Puong Ling; Aminuddin, Ab. Ghani; Nor Azazi, Zakaria (IAHR, INBO & IAHS, 2008)
This paper presents the results obtained from field measurements taken in several frequently flooded equitorial rivers, including velocity distributions,stage discharge relationships, roughness behaviours and discharge estimation. These have illustrated the large difference in velocity between the mainchannel and floodplain under flood conditions, and the effects of momentum transfer between deep and shallow flow, which include reduction in mainchannel velocity and discharge capacity, leading to a reduction in compound section capacity at depth above bankfull. Another significant characteristicthat has been found is that the floodplain regions behave as storage reservoirs (V=0 m/s) in most cases due to high resistance of long and thick grassesalong the flood plains (n=0.07−0.1). Flow resistance relationships have been presented in terms of Manning’s coefficient and Darcy-Weisbachfriction factor, showing the complex nature of flow resistance in the rivers and further explaining the danger inherent in the conventional practicesofextrapolating inbank data for the analysis of overbank flows. Results for discharge estimation have been shown for comparison with actual data, theerrors incurred by applying empirical methods to compound channel flows have been quantified and found to depend on the particular method used